Effect of rotation speed on friction behavior and radially non-uniform local mechanical properties of AA6061-T6 rotary friction welded joint. Issue 18 (17th September 2018) - Li, Xun; Li, Jinglong; Liao, Zhongxiang; Jin, Feng; Xiong, Jiangtao; Zhang, Fusheng
Abstract: The rotary friction welding of AA6061-T6 was conducted and the influence of rotation speed was investigated on friction behavior and on radially non-uniform mechanical properties of AA6061-T6 rotary friction welded (RFWed) joint. The results show that, as the rotation speed increases from 500 to 2100 rpm, the curves of friction time and friction work present like 'V- curve' with a minimum value at 900 rpm and the ratio of friction work in the first stage to that in the whole process increases and then decreases after reaching a maximum value at 900 rpm. The local strength of the joint correlates positively to the thickness of the deformation layer and radially uniform joint is just achieved at 900 rpm. In addition, the maximum local strength of 295 MPa, corresponding to the joint efficiency of 88%, achieves in the peripheral region at 900 rpm.